Overview and Analysis of the Cost of Drug Programs in Poland: Public Payer Expenditures and Coverage of Cancer and Non-Neoplastic Diseases Related Drug Therapies from 2015–2018 Years - Mela, Aneta; Poniatowski, Łukasz A.; Drop, Bartłomiej; Furtak-Niczyporuk, Marzena; Jaroszyński, Janusz; Wrona, Witold; Staniszewska, Anna; Dąbrowski, Jan; Czajka, Anna; Jagielska, Beata; Wojciechowska, Monika; Niewada, Maciej (Frontiers in Pharmacology, 2020)
Background In Poland drug programmes developed by the Minister of Health and financed by the National Health Fund are special reimbursement frameworks of innovative, expensive, and mostly hospital based medical products used for a small number of patients. Research Design The research presented in this paper is based on data analysis published by the National Health Fund in Poland. The analysis focused on estimating public payer expenditure on drugs available within drug programmes from 2015 to 2018. Results In subsequent years, reimbursement of drugs used within drug programmes was associated with the National Health Fund budget expenditure of 635 mln USD, 755 mln USD, 854 mln USD, and 921 mln USD, respectively. Reimbursement of oncology drug programmes constituted 48.1%, 42.5%, 47.1%, and 52.4% and were approximately 305, 312, 402, 483 mln USD, whereas values of non-oncology drug programmes were approximately 330, 434, 452, and 438 mln USD which constituted 51.9%, 57.5%, 52.9%, and 47.6% respectively. Conclusion Despite the fact that the expenditure on drug programs in Poland are increasing every year, they undoubtedly improve the patient’s access to the most innovative oncological and nononcological therapies in the Polish healthcare system.